The Effect of Information Technology on Learning (A Study on Civic and Pancasila Education Students at Mataram University) - Lalu Sumardi; Rispawati; M. Ismail (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2017)
The aim of this research was to know how students completed their academic assignments, the reason why they completed the assignment the way they did, the effects from their choice of approach, and how to solve them. Data collection was done by using documentation, think aloud technique, and focus group discussion. The data analysis was done by using Glaser and Strauss model. The results showed that 91.1% of Civic and Pancasila Education students completed their academic assignments by copying from the Internet. Internal factors consisted of laziness, hedonistic attitude, the tendency to get everything instantly, and lack of awareness about the importance of developing positive mentality and noble character. Meanwhile, external factors consisted of the availability of information on the Internet and the type of task assigned. The effect of such tendency could be categorized into two kinds: short-term and long-term effect. The short-term effect was that the mastery of students’ knowledge was only on the level of “knowing” (C1) and slightly shifted to the level of “understanding” (C2), incomplete and undetailed information about the materials, the materials were not stored in the long term memory, and the students’ way of thinking was not systematic and linear. The long-term effect included the students’ cognitive structure as well as their character which would not be well developed. There were two solutions to address the issue, namely instrumental and mental solution. Instrumental solution included the provision of textbooks, reference books, and the courses’ list of reference books, while mental solution included developing students’ awareness about the importance of scientific way of thinking, building a good attitude and character in everyday’s life, including in the learning process.